Pelatihan Kerja Dan Motivasi Kerja Dalam Upaya Meningkatkan Produktivitas Kinerja Karyawan Di Unit Penerbitan Tebuireng Sub-Unit Majalah - Dio Alif Utama; Hadi Sunaryo; M. Khoirul Anwarudin Broto Suharto (UNIVERSITAS ISLAM MALANG, 2022)
AbstractUnit Magazine Tebuireng is one of the Sub-units of the Issuance of Tebuireng-oriented non-profit. Training and motivation of work that is recognized to be an important factor in improving the productivity performance of the members in non-profit organization named the Magazine Tebuireng. Therefore, the purpose of this research is to analyze to bring up the conclusion of the effectiveness of training and motivation to work in an effort to improve productivity performance of the existing employees in the Magazine Tebuireng.The method of analysis used is Triangulation, the results showed that the training and motivation of work can lead to increased productivity. Keywords : Triangulation, a Sub-Unit of the Magazine, Training, Motivation, Productivity